GLOBAL MIGRATION PROCESS AND ITS INFLUENCE TO THE POLITICAL – ECONOMIC CONDITION OF IMMIGRATING COUNTRIES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This study explores the economic and political impacts of global migration on receiving countries. Using a mixed-methods approach and data from OECD, UN, and World Bank (2015–2025), it analyzes labor market shifts, fiscal effects, and policy responses. Findings reveal migration’s dual role—stimulating economic growth while intensifying political tensions—and propose integrated international strategies for effective migration governance.